Western Balkans Labor Market Trends 2019 - World Bank Group; Vienna Institute for International Economic Studies (World Bank, Vienna, 2019)
This third report on Western Balkan labor market trends presents a descriptive analysis of key labor market indicators for the six Western Balkan countries (Albania, Bosnia and Herzegovina, the Republic of North Macedonia, Montenegro, Kosovo, and Serbia) and selected European Union (EU) countries (Austria, Bulgaria, Croatia, and Hungary) between the second quarter of 2017 and the second quarter of 2018. The report begins with an overview of labor market developments drawn from the Jobs Gateway in South Eastern Europe database and is followed by a special topic on labor costs, labor taxation, and low wages in the Western Balkans.